Reformy dyktuje system – o naradzie oświatowej KC PZPR z 24 października 1958 roku - Król, Joanna (Biuletyn Historii Wychowania, 2013)
The system dictates the reforms – on the educational conference of the Central Committee of the Communist Party on 28 October 1958 The subject of the article is the educational conference which was held on 28 October 1958. It is believed that this meeting, in particular W. Gomulka’s speech, designated the main directions of future educational policy. Gomulka’s speech contained the following conclusions: the extension of compulsory education, the development of vocational education, professionalization of education and ideologisation of teacher training. A very important part of Gomulka’s speech was the issue of teaching religion. Although Gomulka promised to comply with the agreement concluded with the Church on teaching religion, he on the other hand criticized the conduct of the clergy on emblems and religious practices. The participants of the conference were more radical than Gomulka and advocated the total elimination of religious education in school. Strangely enough, all of the main conclusions of the meeting were subsequently turned into legislation. The crowning achievement of the speakers of 1958 became the law on the development of the system of education in 1961, which introduced secular schools and socialist educational ideals.